2014
DOI: 10.1080/10641734.2014.866851
|View full text |Cite
|
Sign up to set email alerts
|

Asian Females in an Advertising Context: Exploring Skin Tone Tension

Abstract: While the explosive literature on the portrayal of women in advertising has established a multitude of salient issues (e.g. sexual objectification), the skin tone of Asian models in ads and associated cultural underpinnings has not yet been examined. However, given the obsession in various Asian countries with skin whitening for women, it has the potential to be salient in Asian cultures in the United States. The current exploratory study examines the possibility of "skin tone tension" occurring in a diverse A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Advertising studies confirm the favorable consumer response to fair-skinned models and skin-whitening products. In general, Asian males evaluated an advertisement more positively when it featured a lighter-skinned than a darker-skinned female Asian (Krishen et al, 2014). Roughly 30 percent of Hong Kong television commercials advertise skin-whitening products (Leong, 2006).…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…Advertising studies confirm the favorable consumer response to fair-skinned models and skin-whitening products. In general, Asian males evaluated an advertisement more positively when it featured a lighter-skinned than a darker-skinned female Asian (Krishen et al, 2014). Roughly 30 percent of Hong Kong television commercials advertise skin-whitening products (Leong, 2006).…”
Section: 3mentioning
confidence: 99%
“…In contrast, they believe darker-skinned Asian women are coarse, unsophisticated and less beautiful menial laborers. First-and second-generation Asian immigrants to Western countries maintain this entrenched fair-skin beauty ideal; for example, US-resident Asians, especially women, desire lighter skin (Krishen et al, 2014). However, this ideal does not pertain to Western culture, as US-residing Caucasians desire darker skin (Krishen et al, 2014) and British men and women do not believe whiteness reflects social status or femininity (Leong, 2006).…”
Section: Chinese Luxury Social Media Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies examining colorism have restricted their research to African American individuals, there is growing evidence for an overwhelming preference for fair skin over dark-skin in Asian countries. "Whiteness" or having white skin is considered an important element in constructing female beauty in Asian cultures (Baumann, 2008;Krishen, LaTour, & Alishah, 2014;Li, Min, Belk, Kimura, & Bahl, 2008). According to Glenn (2008), skin-lightening products are common across many Asian cultures.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the social norms in Chinese culture favouring a fairer skin tone may have somewhat attenuated the preference for high carotenoid colouration, specifically in faces in the Chinese population. Studies have suggested that males and females from Asian regions, including Hong Kong, prefer light skin tones in both the same and the opposite sex (Krishen, LaTour, & Alishah, 2014; Leong, 2006; Li, Min, Belk, Kimura, & Bahl, 2008). And advertisements for face skin-whitening products or medical beauty services are ubiquitous in Hong Kong and other Asian countries.…”
Section: Discussionmentioning
confidence: 99%